Diseño y desarrollo de un sistema de alarma para un vehículo con notificación al teléfono móvil. - Sarango Vega, Michael Esteban (2018)
Insecurity at the national level is the order of the day for different reasons, the economic situation, the lack of police officers, security measures, among others, and the lack of technological tools that are available to users to safeguard personal security and of its assets aggravates the problem. In this virtue, aware of the external threats that increase continuously by crime, a vehicle security system has been designed, which allows the user of the prototype, to know in real time the state of the car through monitoring, through the authorization of a cellular network operator of the market; that works in base to the GLOBAL SYSTEM FOR MOBILE COMMUNICATIONS (GSM) that translated into Spanish is the Global System for the mobile Communications, so that this in turn notifies to its cellular by means of a SHORT MESSAGE SERVICE (SMS), whose translation to the Spanish is The Simple or Short Message Service, so that the system is not only alarm when the vehicle's safety has been violated, but also, so that it immediately reports the incident to the cell phone so that it can effectively react to the minor event. weather. With the above, the present project "DESIGN AND DEVELOPMENT OF AN ALARM SYSTEM FOR A VEHICLE WITH NOTIFICATION TO THE MOBILE TELEPHONE", fulfills the alarm functions for automotive, in search of avoiding or diminishing the risks due to insecurity, since it is connected to a cell phone, allowing to communicate and manage security actions through the GSM cellular network.